AN EFFICIENCY LEAD TIME IN WORKSHOP AREA BASED ON DESIGN TROLY SOLAR CELL - Amani Darma Tarigan (Sean Institute, 2023)
The process of goods movement in distribution channels requires reliable logistics management, to ensure that goods are delivered on time, in the right quantity, in the right quality, and in the right location. Logistics management in distribution channels includes transportation and warehousing. A warehouse is a place to store goods or materials, whether in the form of raw materials, semi-finished goods, or finished goods. Activities in a warehouse include receiving, storing, and shipping goods or materials from one place to the next. The theme taken for this research is related to the storage of goods. The goods stored in the warehouse are numerous and varied. In distributing and storing goods in the warehouse, a tool is needed in the form of a trolley. Currently, the use of trolleys in the warehouse still uses human labor, so it can cause fatigue in humans and lack of time efficiency in the distribution of goods. Therefore, a tool is needed to distribute and store goods in the form of an Arduino-based trolley. In order to meet these criteria, the trolley is able to walk alone according to a predetermined path and can store goods in an empty place.